Sistem Pendukung Keputusan Seleksi Instruktur Pada LKP Karya Prima Menggunakan Metode TOPSIS - Yitro Moarota Harefa; Sinar Sinurat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
LKP Karya Prima is one of the courses and training institutions that has worked closely with several companies to provide quality instructors. To solve the above problems, it is necessary to design an application of a decision support system to assist management in selecting outstanding instructors. Decision Support System (SPK) is used as an alternative application system that helps in making decisions for the determination of outstanding instructors. The process of determining the instructor with precision followed by the availability of more than a few classes that meet certain criteria is including the problem of Multiple Criteria Decision Making (MCDM) TOPSIS, with the application of the TOPSIS method makes management easier to make decisions.